2017
DOI: 10.1097/mao.0000000000001344
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rho/Rho-Kinase Pathway in the Pathogenesis of Cholesteatoma

Abstract: Given Rho-kinase could take essential roles in cell differentiation, the results of this study implicate that down-regulated Rho-kinase could be responsible for the keratinocyte undifferentiation seen in cholesteatoma pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…In our previous study, we demonstrated for the first time that Rho kinase (ROCK-2) protein could be downregulated in the cholesteatoma as demonstrated by Western blotting. 13 In this study, however, we demonstrated that the expression levels of Rho-A, ROCK-1, and ROCK-2 genes were lower in patients with cholesteatoma than in the control group. There was no difference in Rho-A (A/T) and ROCK-1 (G/T) variations in cholesteatoma patients compared to the control indicating that having these variations of both Rho-A and ROCK-1 was not associated with the expression level of Rho-A and ROCK-1.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…In our previous study, we demonstrated for the first time that Rho kinase (ROCK-2) protein could be downregulated in the cholesteatoma as demonstrated by Western blotting. 13 In this study, however, we demonstrated that the expression levels of Rho-A, ROCK-1, and ROCK-2 genes were lower in patients with cholesteatoma than in the control group. There was no difference in Rho-A (A/T) and ROCK-1 (G/T) variations in cholesteatoma patients compared to the control indicating that having these variations of both Rho-A and ROCK-1 was not associated with the expression level of Rho-A and ROCK-1.…”
Section: Discussioncontrasting
confidence: 59%
“…The diminished protein level, which was found in our previous study, may be due to the downregulated ROCK-2 gene expression as has been demonstrated in this study. 13 ROCK-1 variant is localized in upstream region of gene; however, ROCK-2 and Rho-A variant are localized in intron of the gene. Variation in the upstream and intron regions can affect the amount of synthesis without changing the structure of the corresponding protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations